Soft Communication Skills Through Mobile Legends: Exploring Teamwork and Strategy Interaction Among University Students - Amri, Muhammad Agri; Rossi, Muhammad Abiyyu De; Hartati, Rita (CV. Rayyan Dwi Bharata, 2025)
This study investigates the phenomenon of developing soft communication skills through the popular online game Mobile Legends, focusing on university students' teamwork and strategic interactions. The purpose is to explore how collaborative gaming environments facilitate the enhancement of essential communication competencies. Utilizing qualitative methods, including surveys and interviews, the research gathers insights from participants about their experiences in gameplay. Findings revealed that involvement in Mobile Legends significantly improved skills such as effective communication (51.6% effective), teamwork (54.8% effective), strategic interaction (61.3% effective), decision making (51.6% effective), and multi-tasking (48.4% less effective). Thus underscoring the potential of games as a valuable tool for developing interpersonal skills in academic settings.